Moral Judgment and the Perceived Legitimacy of Police Violence against Black People - da Costa Silva, Khalil (2024)
This work analyzes the relationship between moral judgment and racial discrimination in Brazil, operationalized as the perception of legitimacy regarding the use of police violence against Blacks. Study 1 (N = 123) found that racial prejudice predicts the legitimacy of police violence against Blacks and this relationship was moderated by moral judgment. Study 2 (N = 71) identified that police violence against a Black suspect was perceived as more legitimate when compared to a White one. Study 3 (N = 129) found that conventional morality increased the differences between Black and White in legitimacy of police violence, whereas post-conventional morality reduces this difference. In conclusion, the interaction between moral judgment and prejudice explains the racial discrimination in Brazil.